Dietary Phytochemical Screening of Spider Plant (Gynandropsis gynandra (L.) Briq.) Accessions From Africa and Asia to Identify Genotypes for Use in Nutraceutical Breeding - Chataika, Barthlomew Yonas; Akundabweni, Levi Shadeya-Mudogo; Houdegbe, Aristide Carlos; Achigan-Dako, Enoch G.; Sibiya, Julia; Masamba, Kingsley (Frontiers in Sustainable Food Systems, 2021)
Increased public awareness of healthy foods and healthy living, coupled with escalating medicinal costs and recent advances in research and technology, has sparked a paradigm shift to nutraceuticals, which guarantee human health and disease prevention. Spider plants contain dietary phytochemicals with high nutritional and medicinal properties that can contribute to healthy living. A study was conducted to identify spider plant (Gynandropsis gynandra L. Briq) accessions with superior levels of dietary phytochemicals and anti-oxidative activity for use in nutraceutical breeding. Thirty-three accessions of spider plants, representing a wide genetic diversity based on geographic areas of origin (Asia, East Africa, Southern Africa, and West Africa), were used. Total phenolic acids, tannins, and anthocyanins were extracted and quantified using the Folin-Ciocalteau colorimetric, spectrophotometric, and pH differential methods, respectively. Antioxidant activity was determined using phosphomolybdenum method. Results showed significant variation in levels of total phenolic compounds, tannins, anthocyanins, and antioxidant activity (P < 0.05) amongst the spider plant accessions and regions of origin; ODS-15-037 (464 mg TAE/g DW), ODS-15-053 (270 mg GAE/g DW), and BC-02A (127 mg cyanidin-3-glucoside /g DW) had the highest levels of total tannins, phenolic compounds, and anthocyanins, respectively. Antioxidant activity was high in ODS-15-053 (492.2 mg AAE/100 g DW), NAM 2232 (445.3 mg AAE/100 g DW), and NAM-6 (432.5 mg AAE/100 g DW). On average, West African accessions had significantly high tannin concentrations (239 mg TAE/g DW), while Southern Africa accessions contained significantly high anthocyanin content (58.9 mg cyanidin-3-glucoside/g DW). The superior accessions are potential candidates for use in nutraceutical breeding, while the regions of origin could be used as gene pools for specific phytochemicals for improving dietary supplements of nutraceuticals. The strong antioxidant activity exhibited by spider plant accessions suggests the presence of compounds responsible for scavenging free oxygen or nitrogen radicals. Further studies are recommended to identify the chromosomal regions that contain genes controlling the dietary nutraceuticals in the genetic materials and to determine their association with foliage yield and other phenotypes, which can be utilized in spider plant improvement.